2012
DOI: 10.1039/c2em30303e
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of organophosphate esters and brominated flame retardants in German indoor dust samples

Abstract: While it is known that the ingestion of indoor dust contributes substantially to human exposure to the recently restricted polybrominated diphenyl ethers (PBDEs), the situation for one class of potential replacements, i.e. organophosphate esters (OPEs), used in a variety of applications including as flame retardants has yet to be fully characterised. In this study, surface dust from twelve different cars from various locations throughout Germany were analysed for eight OPEs, decabromodiphenyl ethane (DBDPE), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
89
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(113 citation statements)
references
References 27 publications
20
89
2
Order By: Relevance
“…results showed a good agreement with both OPFR and PBDE concentrations previously reported in Australian indoor dust [36,37]. Compared with the concentrations found in other countries, OPFR concentrations here were lower than those in Germany [12], but comparable with those in Netherlands [38], Canada and Kazakhstan [36]. PBDE concentrations in this study were lower than those of the USA [39], but were similar to UK concentrations [40].…”
Section: Australian Indoor Dustsupporting
confidence: 89%
See 1 more Smart Citation
“…results showed a good agreement with both OPFR and PBDE concentrations previously reported in Australian indoor dust [36,37]. Compared with the concentrations found in other countries, OPFR concentrations here were lower than those in Germany [12], but comparable with those in Netherlands [38], Canada and Kazakhstan [36]. PBDE concentrations in this study were lower than those of the USA [39], but were similar to UK concentrations [40].…”
Section: Australian Indoor Dustsupporting
confidence: 89%
“…High detection frequencies and high concentrations of both BFRs and OPFRs were reported in indoor dust which is an important route of exposure, especially for children, since their more frequent hand-to-mouth contact and close-to-ground behaviour could lead to higher amount of dust ingestion, and their lower body weigh results in a higher daily exposure [8]. This has led to an increased interest in levels and distributions of BFRs and OPFRs in indoor dust [9][10][11][12]. Thus, a method capable of simultaneously analysing OPFRs and BFRs in dust is required.…”
Section: Introductionmentioning
confidence: 99%
“…4 Higher concentrations of TDCPP (mean = 130 μg/g) were detected in car dust in Germany. 5 These data suggest that human exposure to TDCPP might commonly occur in some areas. Furthermore, Meeker et al reported a significant correlation between urinary bis(1,3-dichloro-2-propyl) phosphate (BDCPP, a metabolite of TDCPP) and TDCPP concentrations in house dust, 6 suggesting that household dust is an important source for human exposure to TDCPP.…”
Section: ■ Introductionmentioning
confidence: 89%
“…We cited the value of the reference dose (RfD) from previous studies (Ali et al, 2012b;Brommer et al, 2012;Van den Eede et al, 2011). The RfD values were the same in these studies.…”
Section: Intake Assessmentmentioning
confidence: 99%
“…In addition, elementary school students are considered a high-risk group for exposure to house dust because their body weight is lower and they spend more time at home than adults. In recent years (Ali et al, 2012a;Brommer et al, 2012;Stapleton et al, 2009;Van den Eede et al, 2011), studies have shown that intake (both inhaled dust and eaten dust) to PFRs from dust is 2.5 (mean intake) to 4.0 (high intake) times higher for children than for adults.…”
mentioning
confidence: 99%